(untitled) (Ustozlar uchun, 2025)
This article explores the challenges faced by educational classrooms due to the lack of adequate equipment and modern technologies. Many schools struggle with insufficient classroom facilities, limited access to computers, projectors, and other technological tools, which creates barriers to effective teaching and learning. The absence of these resources prevents teachers and students from engaging with innovative and interactive educational methods, leaving them unprepared to compete in a rapidly advancing digital world. The article emphasizes the importance of investing in classroom infrastructure and modern tools to enhance the quality of education and ensure that future generations are equipped to thrive in a technology-driven global landscape.